FROM MOSCOW TO ATHENS THROUGH SCANDINAVIA BY TRAIN - Vlachopoulos, John (Polydynamics Inc, 2025)
Inspired by a real journey undertaken by the author in 1977, this travelogue includes historical iinformation, personal observations, experiences and pictures in various cities and locations: Russia, Finland, Sweden,Germany, Poland, Austria, Hungary, Czechia, Switzerland, Italy, Greece. Topics include the Russian revolution, Russo-Finish war, World war II, Siege of Vienna, ancient Rome and renaissance in Italy, ancient Greek history, Greek civil war.
Keywords: Historical travelogue, pictures , Russia, Finland, Sweden, Germany, Poland, Austria, Hungary, Czechia, Switzerland, Italy, Greece